2021
DOI: 10.31635/ccschem.020.202000318
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Adhesive Materials from Natural Acids and Sugars with Tough and Organic Solvent-Resistant Adhesion

Abstract: Natural adhesives have been widely replaced by industrial adhesives made from petroleum-based products. Compared with that of traditional natural adhesives, modern industrial adhesives show improved adhesion performance. However, the drawbacks of modern adhesives, including toxicity and nonbiodegradability, drive the need for new and high-performance adhesive materials from renewable and biocompatible natural feedstock. In this study, a new family of acid-sugar adhesive materials exhibiting excellent and long-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 49 publications
0
40
0
Order By: Relevance
“…A recent report from Wu et al demonstrated how the molecular and structural features of supramolecular polymeric adhesives can be manipulated to increase adhesion or cohesion and promote debonding. 107 The authors synthesized supramolecular polymeric adhesives from naturally occurring acids and sugars ( Fig. 5a ).…”
Section: Debonding Substrates With Thermal Energymentioning
confidence: 99%
“…A recent report from Wu et al demonstrated how the molecular and structural features of supramolecular polymeric adhesives can be manipulated to increase adhesion or cohesion and promote debonding. 107 The authors synthesized supramolecular polymeric adhesives from naturally occurring acids and sugars ( Fig. 5a ).…”
Section: Debonding Substrates With Thermal Energymentioning
confidence: 99%
“…To combine the virtue of thermoplastic and thermoset hot melt adhesives, hot melt adhesives constructed by dynamic bonds, − including dynamic covalent bonds and noncovalent interactions, have been developed. − Through the continuous reversible rupture or exchange of dynamic bonds, the adhesives can wet the surface of the substrates and join the substrates together. Supramolecular adhesives are made of small molecules or polymers which are connected together through noncovalent interactions to form cross-links. − Owing to the high thermodynamic stability and the rapid kinetic reversibility of noncovalent interactions, − supramolecular hot melt adhesives exhibit multiple reusability and require relatively moderate bonding conditions. , Nevertheless, the unsatisfied adhesion strength restricts the application of supramolecular hot melt adhesives. To impart supramolecular hot melt adhesives with remarkable stiffness and strength, the highly cross-linked architecture is usually designed because of the relatively weak noncovalent interactions .…”
mentioning
confidence: 99%
“…utilized two natural acids, L-(−)-malic acid or citric acid to replace water to prepared supramolecular adhesive materials with D-(+)-trehalose, D-(+)-glucose, D-(+)-fructose, and sucrose, respectively. The formation of hydrogen bond networks between natural low-molecular-weight acids and sugars by mixing and heating simply led to polymerize intensively so as to elicit the strong cohesion effects [ 95 ]. Lan et al.…”
Section: Multi-components Assembled Systems Based On Nsmsmentioning
confidence: 99%
“…Gel–gold NP as an emerging hybrid material could be in situ prepared by exploiting sodium/potassium betulinates, or arjunolic acid under mild conditions, which applied in the development of rapid test strip for biological labelling [ 31 , 67 ]. A family of natural acid–sugar adhesive materials with organic solvent-resistant and tough adhesion effects were developed dramatically as prospective alternatives to polymer adhesives materials [ 95 ]. The self-assembled fiber structures of glycyrrhetinic acid had been employed for the templated growth of semiconductor NPs like CdS, which was particularly advantageous in applying in light emitting diodes, photoelectronic devices, and other industry areas [ 35 ].…”
Section: Applications Of Supramolecular Assemblies Based On Nsmsmentioning
confidence: 99%